2017
DOI: 10.1248/cpb.c17-00409
|View full text |Cite
|
Sign up to set email alerts
|

5,6-Dihydropyrrolo[2,1-<i>a</i>]isoquinolines as Alternative of New Drugs with Cytotoxic Activity

Abstract: In this study, the pyrrolo[2,1-a] isoquinolines 4a-n were synthesized in good yields in a three steps synthesis from the corresponding α,β-unsaturated esters starting materials. These compounds were tested on six human cancer cells lines to measure the cytotoxic activity as a function of the electronic properties and aromaticity of the substituent at the C-2 position of the pyrroloisoquinoline. Our results reveal that the cytotoxic activity could be explained in terms of the distribution of electronic density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…These results confirmed that the cytotoxic activity depends upon the chemical nature of 2-aryl substituents. 86…”
Section: Approach To the Synthesis And Diversification Of Isoquinolin...mentioning
confidence: 99%
“…These results confirmed that the cytotoxic activity depends upon the chemical nature of 2-aryl substituents. 86…”
Section: Approach To the Synthesis And Diversification Of Isoquinolin...mentioning
confidence: 99%
“… Some biological active compounds containing 2,3′-bipyrroles or pyrrolo[1,2- c ]imidazoles moieties [ 24 , 26 , 28 , 30 , 31 , 32 ]. …”
Section: Figure Schemes and Tablementioning
confidence: 99%
“…Therefore, the preparation of pyrroloisoquinoline-bearing compounds can be regarded as a useful and easy way to produce artificial molecules possessing potential bioactivity and pharmaceutical application. 3…”
Section: Introductionmentioning
confidence: 99%